The Effect of Finger-Grip Relaxation Technique on Post Cesarean Section Pain - Shinta Novelia; Tommy J Wowor; Novia Mulia (Health and Technology Journal (HTechJ), 2023)
Background: Complications that occur during pregnancy are one of the triggers for mothers to undergo surgical procedures, one of which is SC surgery. Post-SC surgery patients experience pain due to the incision made during surgery. The aim of this research is to determine pain management using the finger grip relaxation technique. This research was conducted at RSU Prikasih in 2018. A quasi-experiment method with a pre-test and post-test control group design, sampling using accidental sampling of 20 people (10 people in the control group and 10 people in the experimental group). The pain was measured using the Wong Baker Face Rating Scale. Statistical tests use the independent t-test and the paired sample T-Test. Research results show that there was a significant effect of finger grip relaxation on pain in post-SC surgery patients in the experimental group (t=15.05, p=0.000). Finger grip relaxation can reduce pain in post-SC patients. It is hoped that after this research, health workers can use this therapy to reduce pain.